Effect of increasing monensin sodium levels in diets with virginiamycin on the finishing of Nellore cattle - Benatti, João Marcos B.; Alves Neto, João Alexandrino; de Oliveira, Ivanna M.; de Resende, Flávio D. [UNESP]; Siqueira, Gustavo R. [UNESP] (Wiley, 2017)
This study evaluated the effect of increasing levels of monensin sodium (MON) in diets with virginiamycin (VM) on the finishing of feedlot cattle. Two hundred and eighty intact male Nellore cattle (348 ± 32 kg body weight, 22 months) received one of the following five diets: control diet (without additives); diet containing VM (25 mg per kg dry matter) combined with 0 (MON0), 10 (MON10), 20 (MON20) or 30 (MON30) mg MON per kg dry matter. During adaptation (28 days), the MON0 diet increased dietary net energy for maintenance and gain compared to the control diet (P = 0.04). The combination of additives linearly reduced dry matter intake, body weight and average daily gain (P < 0.01). Considering the total study period (110 days), there was a trend of greater net energy intake for maintenance (P = 0.09) and hot carcass weight (P = 0.06) for animals fed MON0 compared to the control diet. The combination of additives linearly reduced dry matter intake (P = 0.04) and linearly increased gain : feed and dietary net energy for maintenance and gain (P < 0.01). The combination of VM with MON at a dose of 30 mg/kg dry matter is recommended for Nellore feedlot cattle because it improves the efficiency of energy utilization.
Keywords: acidosis; carcass; combination of additives; performance